Neoadjuvant PD-1 blockade with sintilimab in mismatch-repair deficient, locally advanced rectal cancer: an open-label, single-centre phase 2 study. (May 2023) - Chen, Gong; Jin, Ying; Guan, Wen-Long; Zhang, Rong-Xin; Xiao, Wei-Wei; Cai, Pei-Qiang; Liu, Min; Lin, Jun-Zhong; Wang, Fu-Long; Li, Cong; Quan, Ting-Ting; Xi, Shao-Yan; et al.
Summary: Background: The current standard treatment for locally advanced rectal cancer is neoadjuvant chemoradiotherapy followed by radical surgery, but this approach can lead to multiple complications. We aimed to investigate the clinical activity and safety of neoadjuvant therapy with sintilimab, a single-agent PD-1 antibody, in patients with mismatch-repair deficient locally advanced rectal cancer. Methods: This open-label, single-arm, phase 2 study was done at the Sun Yat-sen University Cancer Center, Guangzhou, China. Patients aged 18–75 years with mismatch-repair deficient or microsatellite instability-high locally advanced rectal cancer were enrolled and received neoadjuvant sintilimab monotherapy (200 mg by intravenous infusion) every 21 days. After an initial four cycles of treatment, patients and clinicians could choose one of the following options: total mesorectal excision surgery, followed by four cycles of adjuvant sintilimab with or without CapeOX chemotherapy (capecitabine 1000 mg/m 2, orally administered twice daily on days 1–14; oxaliplatin 130 mg/m 2, intravenously administered on day 1 every 3 weeks), determined by clinicians; or another four cycles of sintilimab followed by radical surgery or observation (only for patients with a clinical complete response; also known as the watch and wait strategy). The primary endpoint was the complete response rate, which included both a pathological complete response after surgery and a clinical complete response after completion of sintilimab treatment. Clinical response was evaluated by digital rectal examination, MRI, and endoscopy. Response was assessed in all patients who received treatment at least until the first tumour response assessment, after the first two cycles of sintilimab. Safety was analysed in all patients who received at least one dose of treatment. This trial is closed to enrolment and is registered with ClinicalTrials.gov (NCT04304209 ). Findings: Between Oct 19, 2019, and June 18, 2022, 17 patients were enrolled and received at least one dose of sintilimab. The median age was 50 years (IQR 35–59) and 11 (65%) of 17 patients were male. One patient was excluded from efficacy analyses because they were lost to follow-up after the first sintilimab cycle. Of the remaining 16 patients, six underwent surgery, of whom three had a pathological complete response. Nine other patients had a clinical complete response and chose the watch and wait strategy. One patient had a serious adverse event and discontinued treatment; this patient did not have a complete clinical response and refused to undergo surgery. A complete response was thus noted for 12 (75%; 95% CI 47–92) of 16 patients. One of the three patients who underwent surgery but did not have a pathological complete response showed an increase in tumour volume after the initial four cycles of sintilimab (at which point they underwent surgery); this patient was deemed to have primary resistance to immune checkpoint inhibitors. After a median follow-up of 17·2 (IQR 8·2–28·5) months, all patients were alive and none had disease recurrence. Only one (6%) patient had a grade 3–4 adverse event, which was deemed a serious adverse event (grade 3 encephalitis). Interpretation: The preliminary results of this study suggest that anti-PD-1 monotherapy is effective and tolerable for patients with mismatch-repair deficient locally advanced rectal cancer and could potentially spare some patients from radical surgery. Longer treatment courses might be needed to achieve maximum effects in some patients. Longer follow-up is also needed to observe the duration of response. Funding: The National Natural Science Foundation of China, CAMS Innovation Fund for Medical Sciences, Science and Technology Program of Guangzhou, and Innovent Biologics.